Method for profile reconstruction of the workpiece surface during groove micromilling - Gołaszewski, Marcin; Fiszer, Patryk; Powałka, Bartosz (Frontiers in Mechanical Engineering, 2024)
A leading trend in modern industry is hybrid manufacturing methods. The intention is to integrate additive and subtractive methods into a single machine. In such a process, it is difficult to evaluate the quality of the manufactured component between successive processes. A solution that would make it possible to determine the quality of a component produced by incremental technologies on the basis of forces recorded in a machining process is not yet available. In the present study, an attempt was made to reconstruct the surface of the machined workpiece solely on the basis of recorded forces during the groove micromilling process. A workpiece with a known surface geometry in the form of a sinuous wave was machined. The geometry of the workpiece corresponded to a structure typical of the selective laser sintering method for metallic powders. A process conducted with two different axial cutting depths was considered. The reconstructed surface profiles were evaluated by comparative analysis with the real machined surface.